Monitoring the agri-food System in Myanmar: The rising costs of diets and declining purchasing power of casual wage laborers: June 2020–August 2023 - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2023)
We assess changes in food prices and purchasing power of casual wage laborers based on largescale surveys of food vendors (fielded from June 2020 until August 2023) and households (fielded in 5 periods in 2022 and 2023) in rural and urban areas and in all state/regions of Myanmar. Key Findings  Over the full period (June 2020 - August 2023), the cost of the healthy diet rose by 111 percent and the common diet by 130 percent.  After a reprieve from high food inflation in the first half of 2023, prices increased rapidly in Q3 resulting in a 23 and 27 percent increase in the healthy and common diets, respectively, in August 2023 compared to the previous year, when food prices were already very high.  Rice – the major staple – prices increased by 67 percent between August 2022 and August 2023.  Over the full period (June 2020 to August 2023), pulse, pork, and leafy green prices approximately doubled; rice prices nearly tripled; potato and onion prices more than tripled; and oil prices more than quadrupled.  The value of daily wages of construction and agricultural wage laborers relative to common and healthy diet costs declined by about 18 and 16 percent between the Q2 of 2022 and Q2 of 2023. However, rising wages increased more rapidly in the first half of 2023 while food inflation slowed which stabilized diet adjusted wages.  Food costs outpaced wages between Q2 of 2022 and Q2 of 2023, making food increasingly unaffordable for wage earners who are among the most vulnerable household groups in Myanmar, particularly in rural areas. Recommended Actions  Food should be available at low costs to avoid food security and nutrition problems in the country; assuring a well-functioning agri-food system should therefore be a priority for all stakeholders.  As casual wage workers are among the poorest and as their situation is worsening, they should be targeted in social safety net programs.